The Implementation of the Jigsaw Technique to Increase Students’ Listening Achievement and Motivation Aspects - Doni Alfaruqy (ELE Reviews: English Language Education Reviews, 2021)
Teaching listening needs improvement because many students get low scores on the listening test. This condition should be improved by providing a new teaching technique. Students in Mutiara Senior High School have problems in mastering a listening skill. They are difficult to catch the meaning while the listening test is given. The purposes of this study are to find out whether there is a significant increase after being taught by jigsaw technique and which motivation aspects (effort, goal, persistence, and frequency) have the most influence on students’ achievement in learning English. This experimental study was measured by pretest and posttest designs. The research subject was class XI of science class in even semester of Mutiara Senior High School in South Lampung. The instrument to measure students’ listening achievement was a listening comprehension test which consisted of 30 multiple choices. Another instrument was a close-ended questionnaire with 20 questions to know which motivation aspect had the most influence on students’ English achievements. The data were analyzed by using the t-test formula. The computation result showed that t-ratio in the experimental class had a significant increase from pretest (49.13) to posttest (71.45) after being taught by the jigsaw technique. The result of the computation showed that the value of the two-tailed significance was 0.000. Since the sign < α (0.000 < 0.05), the value indicated that the numbers represented the significance. It means that the treatment given had a better effect on students’ ability. In addition, it revealed that the most influential motivation aspect was an effort. Therefore, students’ personal or group tasks should be supported by giving rewards and punishment to improve students’ efforts in learning.